Vasoconstrictor Effects in Tooth Interventions in Patients with Reduced Left Ventricular Ejection Fraction: Tooth-HF Study - Quaresma, Sergio Eduardo Tricta; Guimaraes, Guilherme Veiga; Neves, Ricardo Simões; Oliveira, Maria Cristina Marino de; Neves, Itamara Lucia Itagiba; Gruppi, Cesar José; Bocch, Edimar Alcide (Cardiology and Cardiovascular Medicine, 2020)
Objectives: The use of a local anesthesia solution with vasoconstrictor for the dental procedure of patients with heart disease is controversial since it could generate adverse cardiovascular risk. Also, its safety has not been investigated in heart failure (HF) patients. This study sought to determine the efficacy and safety of a vasoconstrictor in dental interventions in heart failure (HF) patients with left ventricular reduced ejection fraction (HFrEF) and optimized treatment. Study Design: prospective, parallel group, controlled, double-blind study (Tooth HF study). Materials and Methods: HF patients with ejection fraction <45% and with optimized therapy were randomized to dental intervention using anesthesia solution lidocaine without epinephrine (LSE) or anesthetic solution lidocaine with epinephrine (LCE). The primary endpoint was pain during the intervention. Results: Seventy-two patients were randomized to LSE (n=36) or LCE (n=36). A high prevalence of poor oral health was observed. Reduced pain was observed in LCE patients during dental extraction but not during dental restorations. Ten LSE patients had pain versus 4 LCE patients (p=0.037). No differences between the LSE and LCE patients were observed concerning 24-hour monitored systemic blood pressure, heart rate, and arrhythmia. However, systemic blood pressure increased, and heart rate significantly decreased in relation to the baseline phase during and after the procedure in both groups. Conclusion: Association of local anesthesia with a vasoconstrictor was more effective for pain control in HFrEF patients without compromising safety. These results will benefit millions of HFrEF patients around the world in need of dental intervention.